Dominant PRPF31 Mutations Are Hypostatic to a Recessive CNOT3 Polymorphism in Retinitis Pigmentosa: A Novel Phenomenon of “Linked Trans-Acting Epistasis” - Rose, Anna M (Ann Hum Genet, 2013)
Mutations in PRPF31 are responsible for autosomal dominant retinitis pigmentosa (adRP, RP11 form) and affected families show nonpenetrance. Differential expression of the wildtype PRPF31 allele is responsible for this phenomenon: coinheritance of a mutation and a higher expressing wildtype allele provide protection against development of disease. It has been suggested that a major modulating factor lies in close proximity to the wildtype PRPF31 gene on Chromosome 19, implying that a cis-acting factor directly alters PRPF31 expression. Variable expression of CNOT3 is one determinant of PRPF31 expression. This study explored the relationship between CNOT3 (a trans-acting factor) and its paradoxical cis-acting nature in relation to RP11. Linkage analysis on Chromosome 19 was performed in mutation-carrying families, and the inheritance of the wildtype PRPF31 allele in symptomatic–asymptomatic sibships was assessed—confirming that differential inheritance of wildtype chromosome 19q13 determines the clinical phenotype (P < 2.6 × 10(−7)). A theoretical model was constructed that explains the apparent conflict between the linkage data and the recent demonstration that a trans-acting factor (CNOT3) is a major nonpenetrance factor: we propose that this apparently cis-acting effect arises due to the intimate linkage of CNOT3 and PRPF31 on Chromosome 19q13—a novel mechanism that we have termed “linked trans-acting epistasis.”